Importancia de la gestión del docente en el uso didáctico del celular en el séptimo año de educación general básica de la Unidad Educativa Ana Páez de la ciudad de Latacunga - Andrade Molina, Santiago Israel (2016)
This research was conducted at "Ana Paez" Educative Unit in the academic year 2015-2016; with the students’ collaboration in the seventh year of basic education, taking into account the management carried out by the teacher to adequate and educational use with the cell-phone. Since, a cell-phone is a basic tool of information and innovation that’ is technology transforming. Which the research objective is to encourage teachers and students about the educational applications of technology taking into account cell-phones in school hours by a creative CD in which, there are some different applications for cell-phone for students teaching learning process, cell-phone contribute to develop students’ academic level….